Tool path generation in pocket machining considering workpiece deformation using Finite Element Method (FEM) - Koki KURODA; Hidenori NAKATSUJI; Isamu NISHIDA (Journal of Advanced Mechanical Design, Systems, and Manufacturing)
The metalworking industry is currently facing a shortage of human resources. Furthermore, there is a need for a shift to mass customization, which enables low-volume production at a cost equivalent to that of mass production. To satisfy the demand, it is necessary to increase labor productivity per worker by shortening production lead times. Automated tool path generation is one of the means to reduce production lead time. However, the generation of NC programs that enable high-precision machining requires enormous amounts of time and labor, since it is necessary to modify the NC programs according to the results of test cutting and reviewing the machining conditions. One of the factors causing machining errors in cutting is considered the deformation of the workpiece due to the clamping in a vise. Hence, even if dimensional tolerance measured on the machine is satisfied, dimensional errors may occur when the workpiece is removed from the vise. The purpose of this study is to realize the automated NC program generation for high-precision pocket machining. This study developed a system that predicts the elastic deformation of the workpiece due to the clamping force using Finite Element Method (FEM) and automatically generates a tool path for machining that satisfies the dimensional tolerance when the workpiece is removed from the vise. As a result of case study, it was confirmed that the proposed system can automatically generate tool paths that improves machining accuracy.